Vizualizacija vektorskih polj v fiziki z uporabo barvnih kombinacij - Ambrožič, Milan (Obzornik za matematiko in fiziko, 2012)
We provide a novel way for the visualization of the directions of the vector fields with the RGB color system. The three axes of Cartesian coordinate system are assigned with three colors (R = red for ?$x$?-axis, G = green for ?$y$?-axis and B = blue for ?$z$?-axis). The direction of a vector in each point can then be characterized with a proportional mixing of these colors. As a representative example we show various setups of electric and magnetic fields, the tornado's velocity field and some nematic liquid crystal structures. It turns out that using this technique, the structure and characteristics of a physical systems can be visualized clearly, particularly when stics are added to the colored background.
Keywords: electric field; električno polje; fizika; magnetic field; magnetno polje; physics; RGB barvni sistem; RGB color system; vector field; vektorsko polje; visualization; vizualizacija